The mass of Albireo Aa and the nature of Albireo AB: new aspects from Gaia DR2 - Bastian, Ulrich; Anton, Rainer (Astronomy and astrophysics, 2018)
Aims. We aim to clarify the nature of Albireo AB and specifically to decipher whether it is an optical or physical pair. We also try to determine the mass of Albireo Aa.Methods. We scrutinize and compare the available absolute astrometric data (from HIPPARCOS and Gaia DR2) of Albireo A and B, and we investigate the relative orbit of the pair Albireo Aa,Ac using orbit solutions based on ground-based interferometric measurements.Results. The mass of Albireo Aa (K3 II) is surprisingly small; only an upper limit of about 0.7 M⊙ could be derived. The systemic proper motion of Aa,Ac differs from that of component B by about 10 mas year−1 with an uncertainty of less than 2 mas year−1. Albireo AB is therefore most probably an optical double.Conclusions. Specific astrometric and spectroscopic follow-up observations clarifying the surprising mass estimate for Albireo Aa are recommended.
Gesehen am 13.02.2019